THE EFFECT OF BRAND VALUE ON MARKET CAPITALIZATION: AN EMPIRICAL STUDY ON BANKING INDUSTRY (International Journal of Innovative Technologies in Economy, 2025)
The research objective was to determine the impact of the brand value on market capitalization of a group of banks. This type of research is quantitative. The data analysis method uses the panel data regression analysis method, with fixed effect model (FEM) of sample of five banks for the period from 2009 to 2024. All the data used in this study were collected from bank’s financial statements, in addition to Brand Finance reports. Main findings of this research indicates that brand value has significant negative effect on market capitalization. In contrast, control variables Return on Assets (ROA), has a significant positive impact on the market capitalizations of the banks during the study period. However, the coefficient for GDP findings points out that within the context of this study, the GDP did not contribute positively the banks' market capitalization. In fact, the relationship was negative. In contrast, the control variables included ROA had a significant positive impact on the market capitalization of the banks. This suggests that banks' profitability (ROA) is more influential in driving market capitalization during the study period.